THE INFLUENCE OF THE MOTOR VEHICLE TAX COLLECTION SYSTEM (PKB) ON TAX COMPLIANCE IN THE CITY OF BANDUNG (CASE STUDY OF MOTORIZED VEHICLE TAXPAYERS IN MOBILE SAMSAT S ERVICES REGION I PAJAJARAN CITY OF BANDUNG) - Astri Aryanti; Hafied Noor Bagja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The purpose of this study was to determine the effect of a motor vehicle tax collection system (PKB) on taxpayer compliance in the city of Bandung. This research method uses quantitative research methods. The source of this research uses primary data and secondary data. This research data collection using a questionnaire. The sample of this research is 100 PKB taxpayers in Region I Pajadjaran City of Bandung using accidental sampling. Technique Data analysis was carried out by descriptive analysis and regression analysis. The results of this study indicate that there is a positive and significant effect between the implementation of the motor vehicle tax collection system (PKB) through mobile SAMSAT on taxpayer compliance in the city of Bandung, where the variable implementation of the motor vehicle tax collection system (PKB) through mobile SAMSAT services has an effect of 83.6% and the remaining 16.4% is influenced by other variables not observed in this study.